Sero-prevalence of visceral leishmaniasis by using two diagnostic kits (rKE16 and rK39) - Suliaman AL-Khayyt, Safa.N.; AL-Qadhi, Ban N. (Iraqi Journal of Science, 2023)
The dipstick test was evaluated for sero-diagnosis of visceral leishmaniasis. We compared two types of dipstick (rKE16, rK39) tests . The sensitivity of both tests were determined using sera from fifty-two children suspected of having visceral leishmaniasis and thirty healthy children as a control group collected from Central Teaching Hospital of Pediatric in Baghdad. Fifty (96.15%) cases were confirmed to have infection by rKE16 dipstick test while, fourty-six (88.46%) cases were positive by rK39 dipstick test. Non of the sample taken from healthy control showed reactivity in any of these tests. The study indicated that rKE16 test had better sensitivity than rK39 in the diagnosis of VL(100%) ,(92 %) respectively.